Islamophobia and Its Implications for Islamic Religious Education in Indonesia - Tarbyatul Uluwiyah; Moh. Sugeng Solehuddin; Abdul Khobir; Sopiah Sopiah (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the phenomenon of Islamophobia and its implications for the implementation of Islamic Religious Education in Indonesia. The research employs a literature review method by examining various relevant sources, including books, scholarly journal articles, and research reports. The findings indicate that Islamophobia influences the implementation of Islamic religious education in several ways, such as the emergence of negative stigma toward Islamic religious education teachers, restrictions on certain learning materials, and psychological pressure experienced by Muslim students. In addition, this condition may weaken public support for religious education and potentially lead to misunderstandings among religious communities. Therefore, strengthening the role of education through the integration of multicultural values, the improvement of Islamic literacy, and the promotion of tolerant attitudes is essential for fostering harmonious social relations.